Pathomechanism of Insulin Resistance in Men with Central Obesity: Correlation of GGT, GPx, hs-CRP and Plasma Total Cysteine - Ritawaty Ritawaty; Indriyanti Rafi Sukmawati; Ilhamjaya Patellongi; Ferry Sandra (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Gamma glutamyltransferase (GGT) was reported recently to be associated with inflammation, oxidative stress and increased amino acid. However, role of GGT in insulin resistance pathomechanism is not exactly known. Therefore correlation of GGT with inflammation, oxidative stress and elevated amino acid, in men with central obesity need to be confirmed.METHODS: A cross-sectional study was designed. Men with central obesity were recruited and selected. Anthropometric parameters, creatinine, hs-CRP, fasting glucose, fasting insulin, glutathione peroxidase (GPx) activity, GGT, plasma total cysteine (tCys) and fatty liver were measured. Subjects were then divided in 4 groups based on waist circumference (WC) and fatty liver: Group I: WC ≤100 cm, without fatty liver; Group II: WC ≤100 cm, with fatty liver; Group III: WC >100 cm, without fatty liver; Group IV: WC >100 cm, with fatty liver. All biochemical characteristics in each group were then statistically analyzed.RESULTS: Seventy-two men with central obesity were selected. Numbers of subjects in each group were: Group I: n=33; Group II: n=5; Group III: n=17; Group IV: n=17. We found significant difference of HOMA-IR between Group I and IV, significant correlation between GGT and HOMAIR, and significant negative correlation between tCys with HOMA-IR in Group IV.CONCLUSION: GGT was significantly correlated with HOMA-IR in men with WC >100 cm and fatty liver. Further investigation with more subjects is necessary to determine clear GGT cut-off to distinguish subjects with fatty liver and insulin resistance.KEYWORDS: GGT, hs-CRP, GPx, tCys, HOMA-IR, insulin resistance